1993
DOI: 10.1063/1.109963
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional hybrid model of inductively coupled plasma sources for etching

Abstract: Inductively coupled plasmas (ICPs) are currently being investigated as high density (> lo"-10" cmB3), low pressure (< l-20 mTorr) sources for semiconductor etching and deposition. We have developed a two-dimensional (Y,z) hybrid model for ICP sources and have used the model to investigate Ar/C!Fd02 mixtures for etching applications. The simulation consists of electromagnetic, electron Monte Carlo, and hydrodynamic modules with an "off-line" plasma chemistry Monte Carlo simulation. The model produces the tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 10 publications
0
97
0
Order By: Relevance
“…5,8,9 These studies and several modeling efforts [10][11][12][13][14] show an azimuthal rf electric-field amplitude that is null on axis, increases radially to a maximum value under the antenna, and then falls to zero at the radial boundary. Optical emission was found to peak in the region of peak electric-field amplitude as energy coupling to the electrons is maximum there.…”
Section: Introductionmentioning
confidence: 83%
“…5,8,9 These studies and several modeling efforts [10][11][12][13][14] show an azimuthal rf electric-field amplitude that is null on axis, increases radially to a maximum value under the antenna, and then falls to zero at the radial boundary. Optical emission was found to peak in the region of peak electric-field amplitude as energy coupling to the electrons is maximum there.…”
Section: Introductionmentioning
confidence: 83%
“…To eliminate other factors affecting the accuracy of the solution we did not apply the so-called semi-implicit treatment [22,23,24] for Poisson's equation to circumvent the time step restriction. Instead, a fixed 17 time step ∆t = 10 −9 is imposed.…”
Section: Methodsmentioning
confidence: 99%
“…Then for h ≥ D, we estimate the terms of (22). As an example, the estimation process of I 1 is presented.…”
Section: Consistencymentioning
confidence: 99%
“…The plasma quantities are generated by iterating between these different coupled modules. A short review of these three modules is given in the following, more details can be found in the publications of Kushner et al, the developers of the HPEM [37][38][39][40][41][42]. After defining the reactor geometry and initial operating conditions, the first module EMM calculates the electromagnetic fields within the reactor volume by solving Maxwell equations.…”
Section: The Hybrid Plasma Equipment Modelmentioning
confidence: 99%
“…To investigate the plasma chemistry for a CNT-PECVD system, a systematic study with the 2D Hybrid Plasma Equipment Model (HPEM) [37][38][39][40][41][42] is carried out in our group. An ICP reactor, more specifically, a transformer coupled plasma (TCP) reactor is used in the simulations for two reasons: first, the TCP system is widely used in the semiconductor industry, because it is simple to construct and offers high ionization efficiency compared to dc or RF capacitive discharges.…”
Section: Introductionmentioning
confidence: 99%